THE ROLE OF DYNAMIC CAPABILITY IN IMPROVING SUSTAINABLE PERFORMANCE: MEDIATION OF ENVIRONMENTAL SOCIAL GOVERNANCE (ESG) STRATEGY IN PALM OIL COMPANIES IN MEDAN - Della Andriyani Ridwan; Sambas Ade Kesuma; Narumondang Bulan Siregar (CV. Radja Publika, 2025)
This study investigates the role of dynamic capabilities, specifically absorptive capability and adaptive capability, in enhancing sustainable performance, with Environmental, Social, and Governance (ESG) strategy as a mediating variable. Using an empirical approach, data were collected from 100 employees of palm oil companies operating in Medan, Indonesia, through a full sampling method. Data analysis was conducted using SPSS for descriptive statistics and SmartPLS for Partial Least Squares Structural Equation Modeling (PLS-SEM). The results confirm the significance of all five hypothesized relationships, indicating that both absorptive capability and adaptive capability have a positive effect on sustainable performance, with ESG strategy serving as a mediating variable. Among the two capabilities, adaptive capability has the strongest direct and indirect influence, while absorptive capability shows the weakest effect. These findings provide empirical support for the dynamic capability framework and confirm the validity and reliability of the measurement instruments used. This study contributes to the literature on sustainable business practices in emerging markets, particularly within resource-based industries. Additionally, it offers practical implications for corporate managers, policymakers, and stakeholders by highlighting the strategic value of enhancing dynamic capabilities to drive ESG integration and long-term sustainable performance.